2019
DOI: 10.2147/cia.s195824
|View full text |Cite
|
Sign up to set email alerts
|

<p>Depression in elderly patients with hearing loss: current perspectives</p>

Abstract: Hearing loss (HL) is highly common in older adulthood, constituting the third most prevalent chronic health condition in this population. In addition to posing a substantial burden to disease and negatively impacting quality of life, an emerging literature highlights that HL is associated with unipolar depression including among older adults. This review outlines evidence examining the HL and depression relationship as well as clinical implications for assessment and treatment of comorbid depression and HL. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
2
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 86 publications
1
95
2
11
Order By: Relevance
“…For instance, studies across the globe have demonstrated that people with visual impairment are more likely to experience depression [7,8], and there appears to be a doseresponse relationship with more severe visual impairment linked to a higher prevalence of depression [9]. People with physical impairments or hearing loss are also more likely to report poorer mental health, including depression [3,[10][11][12][13][14]. The likely pathway for these associations is that people with sensory or physical impairments experience difficulties in activities and functioning, which have consequences for reduced perceived control, lower social connectedness, and worse financial circumstances, which all increase the risk of depression and other mental health conditions [2,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, studies across the globe have demonstrated that people with visual impairment are more likely to experience depression [7,8], and there appears to be a doseresponse relationship with more severe visual impairment linked to a higher prevalence of depression [9]. People with physical impairments or hearing loss are also more likely to report poorer mental health, including depression [3,[10][11][12][13][14]. The likely pathway for these associations is that people with sensory or physical impairments experience difficulties in activities and functioning, which have consequences for reduced perceived control, lower social connectedness, and worse financial circumstances, which all increase the risk of depression and other mental health conditions [2,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…hearing impaired with hearing aids and HC. In the elderly population with HL, up to 20% of subjects report a clinically relevant level of depressive symptoms that would require treatment 40 . Both cross-sectional and longitudinal studies indicate that HL is related to the increase in depressive symptoms, although the strength of the association varies between studies.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, institutionalization in residences is associated with factors that can favor the appearance of depressive symptoms and can increase the prevalence of this problem. This is combined with the comorbidity of diseases and decreased health in the older persons (Landi et al, 2004) which is also associated with the onset of depression, especially disorders related to the deficiency of some sense (Camacho-Conde, 2009;Cosh et al,, 2019;Chou & Chi, 2004;Kim et al,, 2011;Singh & Lee, 2019;Wu et al, 2017) or urinary incontinence (Boi et al, 2012). Also, hearing loss increases the risk of neurocognitive impairment (Loughrey et al, 2020).…”
Section: La Relación Entre Depresión Y Deterioro Cognitivo En Personamentioning
confidence: 99%